Assessment and care of visuospatial disorientation in a mixed dementia patient: a case study using objective measurements. Issue 4 (29th September 2015) - Yamada, Eri; Yatokoro, Kaoru; Yamakawa, Miyae; Yayama, So; Shigenobu, Kazue; Taniguchi, Norio; Makimoto, Kiyoko
Abstract: We present a case of a mixed dementia patient with visuospatial disorientation and a developmental disability. The patient was a 69‐year‐old man who was hospitalized for resistance to care, wandering, and a sleep disorder. He was in the advanced stages of dementia and had severe visual impairment due to cataracts. We used an integrated circuit monitoring system and Actiwatch to measure the distance moved per day and sleep–rest cycle, respectively. We administered a coloured paper test to assess the colour most easily recognized by the patient, which was red. We found that displaying his name in large red letters by his door enabled the patient to read his name. We also moved him to a private room next to the day room. The distance moved per day decreased significantly after the implementation of the care plan. However, after the room change, large urine spills were often observed in the bathroom, indicating visuospatial problems. We placed red adhesive tape onto the toilet bowl to make it more visible, which solved the urine spill problem. This case study demonstrates the efficacy of using simple assessment techniques to identify the remaining abilities of a dementia patient and taking simple steps to address the behavioural and psychological symptoms of dementia.